A house is a house for me - Hoberman, Mary Ann.; Fraser, Betty (New York, N.Y. : Puffin Books, 1982)
Lists in rhyme the dwellings of various animals and things.
Originally published: New York : Viking Press, 1978.
School Library Journal
New York Times Book Review
Bulletin Of The Center For Children's Books
2.9
K-3
Keywords: Stories in rhyme; Dwellings -- Fiction; Stories in rhyme; Houses -- Fiction